Source code : my beginnings [large type] - Gates, Bill, 1955- (Random House Large Print, 2025)
"Source Code is not about Microsoft or the Gates Foundation or the future of technology. It's the human, personal story of how Bill Gates became who he is today: his childhood, his early passions and pursuits. It's the story of his principled grandmother and ambitious parents, his first deep friendships and the sudden death of his bestfriend; of his struggles to fit in and his discovery of a world of coding and computers in the dawn of a new era; of embarking in his early teens on a path that took him from midnight escapades at a nearby computer center to his college dorm room, where he sparked a revolution that would change the world"--